Efficiency of a predictive model for assessing the performance of the simple direct attack in terms of physical and motor abilities of junior fencers - AlHaddad, Noor Hatem; AlTaie, Dhafer Namoos; Al-Yasiri, Mohammed Jasim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the nature of the relationship between the performance of the skill of simple direct attack of the fencers and their physical and motor abilities, and also to build a predictive model for the performance of the skill of the simple direct attack of the fencers by knowing the efficiency of their physical and motor abilities for this performance. We used a descriptive, correlational, and survey approach to collect and analyze the data. The tests were applied on 40 fencers from the junior category (under 17 years old) in Diyala and Baghdad Clubs during the 2017-2018 season. The Statistical Package for the Social Sciences (SPSS) was used for statistical analysis. The majority of relationships between the results of the performance of the simple direct attack skill of the fencers and their physical and motor abilities were statistically significant (p < 0.05). So, most of the physical abilities and their various forms, as well as the motor abilities, have great contributions to the performance of the skill. We also have found the significance of the model’s coefficients (F = 12.672, p = 0.000), thus showing that the morality of the model confirms its efficiency. In conclusion, the effective relationships of physical and motor abilities were limited to the performance of the simple direct attack skill (straight) of junior fencers in: strength characterized by speed for the two legs, running (20 meters), accuracy, kinetic response, transitional speed with progress, transitional speed by retreat, endurance speed with progress and retreat, and agility. The predictive model did not show an effect of the predictors, although they are good predictors for the performance of the skill of simple direct attack for the fencers.